2020
DOI: 10.1080/02687038.2020.1765304
|View full text |Cite
|
Sign up to set email alerts
|

Information, communication, advocacy, and complaint: how the spouse of a man with aphasia managed his discharge from hospital

Abstract: Background: The impact of stroke and aphasia has been recognised as a family problem for many years with studies highlighting spouses' need for information at different times along the recovery journey, for practical and emotional support, recognition, and respite. In particular, the decision-making around discharge from hospital, or planning for rehabilitation, is not always collaborative even though family involvement assists family members to plan and adjust to their new caring role. Aims: This study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Poor communication about issues concerning their relative in the RACS, including instances of dishonesty or deliberate concealment, also prompted carers to advocate for their family member. Similar reports are found in community aged care literature (Carlsen & Lundberg, 2018) and the literature reporting care of older people in acute care settings (Hersh & Armstrong, 2020), especially when instances of harm occur (Hemsley et al, 2013). A lack of open communication has been shown to be a major reason for distrust in care, leading to greater involvement and monitoring behaviour of families (Haesler et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…Poor communication about issues concerning their relative in the RACS, including instances of dishonesty or deliberate concealment, also prompted carers to advocate for their family member. Similar reports are found in community aged care literature (Carlsen & Lundberg, 2018) and the literature reporting care of older people in acute care settings (Hersh & Armstrong, 2020), especially when instances of harm occur (Hemsley et al, 2013). A lack of open communication has been shown to be a major reason for distrust in care, leading to greater involvement and monitoring behaviour of families (Haesler et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…Information about post‐discharge services was not communicated to them at hospital discharge (Chen et al, 2020). Young people with stroke encountered challenges sourcing post‐discharge age‐appropriate support (Hersh & Armstrong, 2020; Stokman‐Meiland et al, 2020). Shortened hospital stays added more challenges for nurses and multidisciplinary teams to assess and address these issues during discharge planning.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen studies were included in the review. The characteristics of included studies are presented in (Borg et al 2020;Chu et al 2020), evaluating health and disability funding timeframes (Houston et al 2020), understanding the hospital-to-home transition (Biester et al 2016;Conti et al 2016;Hodson et al 2016;Abrahamson et al 2017;Dwyer and Mulligan 2017;Fitts et al 2019;Irgens et al 2020;Hersh and Armstrong 2021), evaluating discharge documentation (Kable et al 2018), evaluation of a transitional care model from hospital to the community (Qian et al 2019), and development of an integrated care pathway for people recovering from stroke (Abdul Aziz et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…New (2015) found that negotiations with family members accounted for 12.8% of barriers to discharge in an SCI unit. Across qualitative studies, close others considered their involvement in the discharge planning process as crucial (Conti et al 2016;Abrahamson et al 2017;Hersh and Armstrong 2021). In two quantitative studies, people with acquired disability and close others were involved in the development and delivery of discharge plans and post discharge rehabilitation programs (Borg et al 2020;Chu et al 2020).…”
Section: People With Acquired Disability and Close Others As Active P...mentioning
confidence: 99%
See 1 more Smart Citation